Farmers’ Willingness to Pay to Women Community Animal Health Workers (CAHWs): A Study of the Pashusakhi Model in Bahraich District of Uttar Pradesh, India - Kumar, Tarun; Chander, Mahesh; Suman, Ram Singh; Kumar, Sanjay; Singh, Madan; Singh, Yash Pal (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Community Animal Health Workers (CAHWs) play a crucial role in delivering basic animal healthcare services in rural areas across many countries particularly in Asia & Africa. The Pashusakhi model in India equipped women from local communities to provide preventive veterinary services, including vaccination and deworming. Understanding livestock farmers’ willingness to pay (WTP) for these services is essential for assessing the economic sustainability and long-term viability of the Pashusakhis. This study aimed to analyse the WTP of livestock farmers for Pashusakhis’ services and identify socio-economic and perception-based factors influencing WTP in Bahraich district of Uttar Pradesh, India. A total of 100 livestock farmers from 10 villages in Chitaura block were randomly selected. WTP was assessed using the Contingent Valuation Method (CVM) under two service delivery scenarios: common village centre and doorstep services. Data were analysed using frequency, mean, percentage, and multiple regression to identify determinants of maximum WTP for doorstep services. Initial willingness to pay was reported by 74 % of respondents for village centre services and 91 % for doorstep services. Mean maximum WTP was ₹ 56.28 for village centre services and ₹ 93.79 for doorstep services. Regression analysis indicated that formal education, annual household income, and income from livestock had a significant positive influence on maximum WTP. Livestock farmers demonstrated clear willingness to pay for preventive healthcare services for animals, with higher value attributed to doorstep delivery due to convenience, time saving, and reduced animal stress